Prevalence and Risk Factors of Uterine Prolapse in Achham District, Nepal - Bogati, Namita Kumari; Aryal, Bhagwan; Kuikel, Jyoti; Bogati, Tilak; Ranabhat, Chhabi Lal (Journal of Health Promotion, 2023)
Uterine Prolapse (UP) is one of the hidden morbidities that do not lead to death, but women suffer from severe lifelong disabilities. In Nepal, the prevalence of UP in women varies from 10 to 40% due to several underlying causes. Therefore, the main aim of the study was to identify the prevalence and associated risk factors of UP. This community-based descriptive cross-sectional study was conducted among 300 married women aged 18 and over in four villages of Kamal Bazar Municipality, Achham, who suffered from UP. The random sampling technique was used to collect the data. The samples were selected using multistage sampling technique. The structured interview questionnaire was used and the face-to-face interview was conducted. The data were analyzed using MS-Excel and SPSS version 23. The statistical tests used were binary logistic regression, univariate and multivariate logistic regression. The prevalence of UP was 33.7%. In the multivariate analysis, participants aged 20-30 were forty one times more likely to suffer from UP than older participants of 50-60 {aOR 41.86 (95% CI; 14.31-122.45)}, were seven times more likely to have not attended health facilities for Antenatal Checkup/Postnatal Checkup (ANC/PNC) {aOR 7.10 (95% CI; 3.53-14.26)}, were less likely to have institutional delivery {aOR 0.13 (95% CI; 0.05-0.31)} and were three times more likely to have high Body Mass Index (BMI) {aOR 3.97 (95% CI; 1.81-8.71)}. Thus, the participants who hadn’t attended ANC/PNC checkups, had given birth at home, or had a high BMI, were more likely to have suffered from UP. Education is necessary to make people aware of UP at an early age and its impact is seen among people of a lower age inthe area.